Model Laboratorium Pengaruh Debit Terhadap Perubahan Morfologi Pada Sungai Berbelok Ganda - Febriani, Vita Dwi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
A series of meanders of natural river, cause helicoidal force. It’s causes bed erosion and attack the river bank on the outside of meander. The laboratory model used to determine the phenomenon of morphological changes in double meandering river with M = 1,2. The bed of model used Kampar sand with grain size d35 = 0,285 mm, d50 = 0,330 mm and d65 = 0,380 mm and Gs = 2,63. The froude number flow used 0,670 and 0,769, while the Reynolds number used 3081,683 and 4381,188 then it’s classified in turbulent flow. The flow pattern on this double meandering channel cause the establishment of a bed configuration uneven on the channal width, as a result of H0/B < 0.05, so that the phenomenon of helicoidal flow cross the channel does not happen and does not add the velocity on the outside of the bend. The bed configuration is formed to follow the direction of a trend of Umaks or on each side of meander. Sediment transport analysis result prove that the higher Froude number is used the bigger the granules are transported.Key word : laboratory model, morphological changes, helicoidal force, velocity distribution, flow pattern, turbulent flow, basic configuration.